2017
DOI: 10.3892/or.2017.5398
|View full text |Cite
|
Sign up to set email alerts
|

Low uptake of fluorodeoxyglucose in positron emission tomography/computed tomography in ovarian clear cell carcinoma may reflect glutaminolysis of its cancer stem cell-like properties

Abstract: The characteristics of ovarian cancers that showed low activation of glycolysis were investigated. Using medical records of patients with ovarian cancers who had undergone fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) prior to their primary surgery at the University of Tokyo Hospital between 2010 and 2015, we identified cases with a low uptake of FDG in PET/CT. We considered the maximum standardized uptake value (SUVmax) as the degree of glucose uptake. We investigated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The cellular uptake of 18 FDG appears to depend partly on cellular grade (17). In ovarian cancer, patients with clear-cell carcinoma have been shown to have a lower mean maximal standardized uptake value than patients with serous adenocarcinoma or endometrioid adenocarcinoma (18)(19)(20). Clear-cell carcinomas seem to prefer the glutaminolysis pathway over glycolysis, resulting in lower 18 F-FDG concentrations in cells and a weaker signal (19).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular uptake of 18 FDG appears to depend partly on cellular grade (17). In ovarian cancer, patients with clear-cell carcinoma have been shown to have a lower mean maximal standardized uptake value than patients with serous adenocarcinoma or endometrioid adenocarcinoma (18)(19)(20). Clear-cell carcinomas seem to prefer the glutaminolysis pathway over glycolysis, resulting in lower 18 F-FDG concentrations in cells and a weaker signal (19).…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrated lower uptake of glucose in ovarian clear cell carcinoma with CSC-like properties on fluorodeoxyglucose positron emission tomography/computed tomography, indicating a low activation of glycolysis [ 123 ]. Further in vitro evaluation found that, in comparison to non-CSCs, CSCs have lower expression levels of LAT1, a transporter of glutamine efflux, and GLUT1, a transporter of glucose influx [ 123 ]. The expression level of SLC1A5 shows no difference, suggesting a comparable glutamine influx between CSCs and non-CSCs [ 123 ].…”
Section: Glutaminolysis In Cscsmentioning
confidence: 99%
“…Further in vitro evaluation found that, in comparison to non-CSCs, CSCs have lower expression levels of LAT1, a transporter of glutamine efflux, and GLUT1, a transporter of glucose influx [ 123 ]. The expression level of SLC1A5 shows no difference, suggesting a comparable glutamine influx between CSCs and non-CSCs [ 123 ]. Taken together, these lines of evidence depict a glutamine-accumulating feature and indicate the metabolic diversion toward glutaminolysis from glycolysis in ovarian CSCs ( Figure 2 ).…”
Section: Glutaminolysis In Cscsmentioning
confidence: 99%
“…Assays of glycolysis and glutamine transporters indicate that ovarian clear cell carcinoma (CCC) displayed low glycolytic flux, which may be related to the high glutaminolysis and its CSC-like properties [ 116 ]. Especially, higher expression levels of ASCT2 and GLS were observed in CSCs, which implicated that ASCT2 and GLS are important for the proliferation and maintenance of the redox state in CSCs [ 114 ].…”
Section: Glutamine Metabolism In Cscsmentioning
confidence: 99%